2016
DOI: 10.3389/fmicb.2016.01960
|View full text |Cite
|
Sign up to set email alerts
|

Gene Turnover Contributes to the Evolutionary Adaptation of Acidithiobacillus caldus: Insights from Comparative Genomics

Abstract: Acidithiobacillus caldus is an extremely acidophilic sulfur-oxidizer with specialized characteristics, such as tolerance to low pH and heavy metal resistance. To gain novel insights into its genetic complexity, we chosen six A. caldus strains for comparative survey. All strains analyzed in this study differ in geographic origins as well as in ecological preferences. Based on phylogenomic analysis, we clustered the six A. caldus strains isolated from various ecological niches into two groups: group 1 strains wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…SCN63-17 clustered together. This result is consistent with the results of an earlier study that found six Novosphingobium strains were correlated with their isolation sources (Gan et al, 2013 ), and in a CV tree of Acidithiobacillus caldus , three strains from a copper mine clustered together (Zhang et al, 2016 ). However, most of the subclades in the phylogenetic trees had more ambiguity in habitat specificity.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…SCN63-17 clustered together. This result is consistent with the results of an earlier study that found six Novosphingobium strains were correlated with their isolation sources (Gan et al, 2013 ), and in a CV tree of Acidithiobacillus caldus , three strains from a copper mine clustered together (Zhang et al, 2016 ). However, most of the subclades in the phylogenetic trees had more ambiguity in habitat specificity.…”
Section: Resultssupporting
confidence: 92%
“…Further analysis showed that when more strains were included in phylogenetic trees, the trend to cluster according to habitat was more mixed. This suggests that specific environment variations also may influence genome structure (Lin et al, 2013 ; Ji et al, 2014 ; Zhang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome functional annotation was performed using the Rapid Annotations using Subsystems Technology (RAST) platform (http://rast.nmpdr.org/) (92). Subsequently, protein sequences and corresponding annotation were acquired as previously described (43,93). PanOCT version 3.18 (94), with an E value cutoff of 0.00001 and sequence identity cutoff of 65%, was applied for the identification of orthologs that were shared between species or strains.…”
Section: Figmentioning
confidence: 99%